2022
DOI: 10.1097/icu.0000000000000849
|View full text |Cite
|
Sign up to set email alerts
|

Brolucizumab for the treatment of diabetic macular edema

Abstract: Purpose of reviewTo review the available data supporting the use of brolucizumab in the treatment of diabetic macular edema (DME).Recent findingsBrolucizumab is a humanized single- chain variable antibody fragment (scFv), the smallest functional subunit of an antibody approved for intravitreal use. Three phase III studies demonstrate that at 52 weeks, brolucizumab has statistically superior anatomical outcomes of reducing retinal thickness (54.0–57.5% of brolucizumab treated eyes achieved central subfield thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 39 publications
0
8
0
2
Order By: Relevance
“…These range from 0.05% to 2.1% for aflibercept, 0.05% to 1.1% for bevacizumab, and 0.005% to 1.9% for ranibizumab. In contrast, it reaches 4.4% for brolucizumab 22 .…”
Section: Brolucizumabmentioning
confidence: 84%
See 2 more Smart Citations
“…These range from 0.05% to 2.1% for aflibercept, 0.05% to 1.1% for bevacizumab, and 0.005% to 1.9% for ranibizumab. In contrast, it reaches 4.4% for brolucizumab 22 .…”
Section: Brolucizumabmentioning
confidence: 84%
“…Brolucizumab, a relatively novel anti-VEGF agent for the treatment of DME, has demonstrated efficacy in reducing macular thickness and has shown significant potential in improving best-corrected visual acuity (BCVA) and central subfield macular thickness (CSMT) in patients with DME 21 . Furthermore, it is possible that fewer injections may be required compared to other anti-VEGF agents 21,22 . The efficacy of brolucizumab has been demonstrated to persist for up to 16 weeks, thereby reducing the treatment burden 22 .…”
Section: Brolucizumabmentioning
confidence: 99%
See 1 more Smart Citation
“…Intraoperative aflibercept did not exert a significant effect on postoperative CMT or visual acuity at 3 months, probably due to a relatively shorter half-life ( 65 ). To date, there are no clinical trials yet examining the role of intraoperative injection of newer anti-VEGF agents, such as brolucizumab and faricimab on DMR, but their safety profiles and efficacies on DME were demonstrated in clinical trials ( 66 , 67 ). Nevertheless, intravitreal anti-VEGF still remains the well-established first-line treatment for preoperative DME ( 68 , 69 ).…”
Section: Management Of Dme and Cataract Surgerymentioning
confidence: 99%
“…The KESTREL and KITE studies demonstrated that intravitreal injection of brolucizumab (IVBr) was effective in the robust gain of visual acuity and anatomical improvement [ 9 ]. Moreover, the intervals of brolucizumab injection are prolonged up to 16 weeks; thus, the treatment burden on patients may be reduced [ 10 ].…”
Section: Introductionmentioning
confidence: 99%